PTU-020 REDUCe study: multi-centre feasibility RCT in cirrhosis-related palliative refractory ascites. participant reported outcomes. (June 2019) - Macken, Lucia; Mason, Louise; Evans, Catherine; Steer, Shani; Bremner, Stephen; Crook, David; Thomson, Sam; Sheridan, David; Isaacs, Peter; Wright, Mark; Hashim, Ahmed; Verma, Sumita
Abstract : Introduction: The REDUCe study is a multicentre feasibility randomised controlled trial (RCT) comparing palliative long term abdominal drains (LTAD) with standard care, recurrent large volume paracentesis (LVP), in advanced cirrhosis and refractory ascites (RA), where ineligible for liver transplant (LT). Limited data exist on symptom burden in this group. Clinical, patient/carer reported, qualitative and health economic (HE) assessments were performed to resolve uncertainties and inform the design of a definitive RCT of LTAD as a palliative strategy in RA. Here we report on patient/carer reported outcomes. Methods: Patients randomised 1:1 (LVP or LTAD). The LTAD group had community nurse home visits for ascites drainage. The LVP arm received standard care attending hospital. Follow up was 12 weeks with home visits every two weeks for clinical and questionnaire-based assessments: palliative care needs/symptom burden (IPOS); quality of life (QoL) (SF-LDQOL) and EQ-5D-5L; carer burden (ZBI-12) and service use. Results: Thirty-six patients were randomised; 19 LVP and 17 LTAD. Uptake of questionnaires was high (>85%). Only 47% of the participants had carers who could complete ZBI-12 (9 LTAD vs 8 LVP). Symptom burden score (IPOS) was comparable in both groups at baseline and 12 weeks follow up. Compared to baseline, the EQ-5D-5L Health index worsened in LTAD but remained stable in LVP group, the reverse being true for the EQ-5D-5L visual analogue scale. SF-LDQoL: baseline domains were higher in the LTAD group, during follow up scores became similar in both groups (data not shown) except in the following domains where LTAD group had lower scores: memory, distress, loneliness and hopelessness. Baseline carer burden (ZBI-12) in LTAD was higher, but remained stable; however, in LVP carer burden was higher at 12 week follow up (table 1 ). Conclusions: Preliminary data from REDUCe confirms and extends findings of significant symptom and carer burden in advanced cirrhosis and RA. LTAD may help mitigate carer burden, which was higher in the LVP group. Results of other PROM (SF-LDQOL and EQ-5D-5L) were variable. This may reflect the timing of questionnaire completion in relation to ascites drainage and large sampling variability. Finally the presence of the LTAD may have been a constant reminder of the palliative nature of the illness. Our results need further validation. Results will inform appropriate QoL assessment tools for definitive RCT design.